Comic pornotopia: the theatricalized fiction of sexuality in Magda, Deus aos domingos and garota Silat - F. Miranda Jr, Edmilson (2022)
This paper employs Paul B. Preciado’s concept of pornotopia, along with Theresa Tensuan’s critical approach to comics, to analyze the representation of the characters Magda, Deus and Garota Silat, created by the comics artist Rafael Campos Rocha. The investigation also employs the perspective of Marlucy Paraíso, in which the three characters are protagonists in cultural texts oriented to leisure and entertainment. Based on the content analysis methodology outlined by Bardin, pornotopias are posited as models of masculinity invented for the production and consumption of pleasure by way of their presence in comics simultaneously reproductive and critical of that very masculinity. In this view, the representation of the female body reproduces Preciado’s theatricalized fiction of sexuality and, at the same time, challenges this fiction through presenting discourses that interface with discourses of decoloniality, questioning hegemonic patriarchal symbolic structures. In this sense, the characters confirm Tensuan’s reading of the comics, offering a vision of performative practices, family rituals and cultural conventions that articulate individual and collective differences in the context in which they are inserted, the context of a Brazil permeated by complex disputes over the culturally constructed concept of gender.